2020
DOI: 10.15252/emmm.202012025
|View full text |Cite
|
Sign up to set email alerts
|

Fate and propagation of endogenously formed Tau aggregates in neuronal cells

Abstract: Tau accumulation in the form of neurofibrillary tangles in the brain is a hallmark of tauopathies such as Alzheimer's disease (AD). Tau aggregates accumulate in brain regions in a defined spatiotemporal pattern and may induce the aggregation of native Tau in a prion-like manner. However, the underlying mechanisms of cell-to-cell spreading of Tau pathology are unknown and could involve encapsulation within exosomes, trans-synaptic passage, and tunneling nanotubes (TNTs). We have established a neuronal cell mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 80 publications
(147 reference statements)
3
40
0
Order By: Relevance
“…Interestingly, our results show that lysosomes containing α-syn fibrils are not targeted for lysophagy [84] (S4 Fig), possibly suggesting a rescue mechanism such as the one orchestrated by the endosomal sorting complexes required for transport (ESCRT) machinery [111,112]. Considering the evidence supporting autophagy impairment in NDs and more specifically following α-syn accumulation [55,113], and the recent findings that impaired autophagic flux contributes to the occurrence of LMP [114], it will be interesting to assess the contribution of autophagy to LMP, lysosomal dysfunction, and propagation of α-syn.…”
Section: Plos Biologymentioning
confidence: 72%
See 1 more Smart Citation
“…Interestingly, our results show that lysosomes containing α-syn fibrils are not targeted for lysophagy [84] (S4 Fig), possibly suggesting a rescue mechanism such as the one orchestrated by the endosomal sorting complexes required for transport (ESCRT) machinery [111,112]. Considering the evidence supporting autophagy impairment in NDs and more specifically following α-syn accumulation [55,113], and the recent findings that impaired autophagic flux contributes to the occurrence of LMP [114], it will be interesting to assess the contribution of autophagy to LMP, lysosomal dysfunction, and propagation of α-syn.…”
Section: Plos Biologymentioning
confidence: 72%
“…TNTs are openended structures [48,49] that allow the exchange of various cargos, including entire organelles, such as mitochondria and lysosomes, between cells [19,[37][38][39][40]. In addition to α-syn fibrils, other amyloidogenic proteins such as prion protein [50][51][52], huntingtin [53], and tau [52,54,55] use TNTs as highways for transfer to naive cells, suggesting that TNTs are common routes for the spread of pathogenic proteins between cells. Of particular interest, we showed that α-syn fibrils can be efficiently transferred between neuronal Cath.a-differentiated (CAD) cells, primary neurons, primary astrocytes, and human neural progenitor cells and between organotypic hippocampal slices and astrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, we and others have shown that extracellular monomeric and fibrillar Tau species induce the formation of TNTs, which facilitate their transfer between neuronal cells (Tardivel et al , 2016; Abounit et al , 2016b). We have also recently shown that endogenously formed Tau aggregates are found in TNTs (Chastagner et al , 2020). Together, these data indicate that proteins involved in Tauopathies and AD could hijack TNTs and use them as a means of spread, as previously described for Prion, α‐syn, and mHTT (Victoria & Zurzolo, 2017).…”
Section: An Overview Of Tunneling Nanotubesmentioning
confidence: 73%
“…What are the fundamental avenues by which tau seeds can propagate from one neuron to another? Propagation can be via extracellular vesicles such as exosomes [10,11,27] or microvesicles [28,29], tunneling nanotubes that establish a direct connection between the cytoplasm of neighboring cells [30,31], transfer of extracellular tau due to mere proximity of cells [15,32,33], or transsynaptic transfer of tau seeds between interconnected neurons [8,10,12,27]. Interestingly, only exosomes [10,27] (Fig 2A ) and vesicle-free tau seeds [8,12] have been shown to propagate transsynaptically (Fig 2B-D), and although tau has been found associated with microvesicles [28,29], to our knowledge there is no study showing that microvesicles can move transsynaptically between interconnected neurons or seed tau aggregation in recipient cells.…”
Section: Neuron-to-neuron Transmission Of Tau Seedsmentioning
confidence: 99%